Metastatic neck node with unknown primary (Bangladesh Journal of Otorhinolaryngology, 2014)
Objective: To find out the clinical presentation of metastatic neck node with unknown primary. Methods: A cross-sectional study done on the admitted patient from four tertiary level hospitals in Dhaka city from January 2010 to September 2010. Results: Most of the cases were squamous cell carcinoma (68.75%). the next common was adenocarcinoma (15.62%) and undifferentiated carcinoma (12.5%). Melanoma was a rare condition (3.13%). The commonest age group was 6th decade (40.63%) which was followed by 5th decade (28%). None of the case was found bellow the age of 30 years. The male to female ratio was 2:1. Commonest metastatic group of lymph node was Level II (50%), followed by Level- III (22%) Level- IV (19%), Level- V (6%) and Level- I (3%). Staging of lymph nodes were N2A (35%), N1 (31%), N2B (16%), N3 (12.5%) and N2C (6.25%) in decreasing order of frequency. About 72% cases are smoker. Conclusion: Metastatic carcinoma with unknown primary tumour commonly present in elderly age group and majority of cases are squmous cell carcinoma. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17631 Bangladesh J Otorhinolaryngol 2013; 19(2): 94-98